Pregnancy Screening before Diagnostic Radiography in Emergency Department; an Educational Review - Abushouk, Abdelrahman Ibrahim; Sanei Taheri, Morteza; Pooransari, Parichehr; Mirbaha, Sahar; Rouhipour, Alaleh; Baratloo, Alireza (Archives of Academic Emergency Medicine, 2017)
Radiation exposure during pregnancy may have serious teratogenic effects to the fetus. In modern medical practice, there is an increasing dependence on imaging techniques in most medical specialties. Therefore, checking the pregnancy status before imaging women of child bearing age is essential. Lack of international regulations and standard protocols exposes the patient to unexpected fetal radiation effects and the health professionals to medicolegal suits. Recently, the American Academy of Radiology and the European community of Medical Ionizing Radiation Protection released national guidelines regarding pregnancy screening before imaging potentially pregnant females. However, different methods of pregnancy screening exist among different radiology centers. This review aims to discuss the most recent guidelines for imaging females of childbearing age and highlight the need for an international regulation to guide pregnancy screening before radiological exposure.